Rancang Bangun Sistem Realtime Notification Progress to Customer Berbasis Website - Novtarina, Dita Aulia; Candra, Feri (P3M Politeknik Negeri Bengkalis, 2024)
PT Agung Automall SM. Amin Pekanbaru is a branch of PT Agung Automall, a company operating in the automotive sector. PT Agung Automall SM. Amin, there are several divisions of work, one of which is the Body Paint (BP) division. Problems that arise in the Body Paint (BP) division is that the current system in Body Paint (BP) is less effective, it's because customers have difficulty knowing the progress of their cars. Customers are required to ask the service advisor to find out the progress of their car service. However, with a work system like this, human error often occurs, such as service advisors forgetting/being late in providing information on customer car service progress to customers. Therefore, a system is needed that can provide WhatsApp notifications of customer car service progress. This system uses the WhatsApp API to send notifications to customers. The design stages of this system use the prototype development method. This research produces a Website-basedÂ Realtime NotificationÂ Progress System that can be used by customers to see the progress of their car. Testing of this system was carried out using black box testing and showed that the system was running well.